Justifications of emotional responses to eliciting situations: A narratological approach to the CAD hypothesis - Song, Chengfang; Rui, Xiaosong; Xie, Nini (Frontiers in Psychology, 2022)
Different from the previous design to establish correlations between emotions and eliciting situations which instantiate moral codes, this paper examined the CAD hypothesis by considering three elements, namely eliciting situations, the emotional responses to them, and justifications of responses, within the appraisal theories of emotion. First, similarity data were collected among the situations by using the Order k/n-1 with fixed K method. Second, the participants were instructed to write down both their responses and justifications of their responses to the situations. Correspondence analyses among the three elements, together with results from the Multidimensional Scaling analysis of the similarity data, showed that the CAD hypothesis is largely supported if mappings are set between the emotions in question and moral judgement concerning the eliciting situations (referred to as basis in the paper), rather than situations themselves, and that the hypothesis is further conditioned by characters (another component of justification).